Bacterial Foraging-Tabu Search Metaheuristics for Identification of Nonlinear Friction Model - Nuapett Sarasiri; Kittiwong Suthamno; Sarawut Sujitjorn (Journal of Applied Mathematics)
This paper proposes new metaheuristic algorithms for an identification problem of nonlinear friction model. The proposed cooperative algorithms are formed from the bacterial foraging optimization (BFO) algorithm and the tabu search (TS). The paper reports the search comparison studies of the BFO, the TS, the genetic algorithm (GA), and the proposed metaheuristics. Search performances are assessed by using surface optimization problems. The proposed algorithms show superiority among them. A real-world identification problem of the Stribeck friction model parameters is presented. Experimental setup and results are elaborated.